Transforming in the Digital Era: Uncovering the Potential of Self-Reliance and Technology for the Success of New UT Students in Distance Learning - Eko Kuswanti; Sri Sukatmi; Lasando Lumban Gaol; Pesi Suryani; Anton Robiansyah (Postgraduate, University of Mataram, 2024)
This study aims to analyze the influence of self-directed learning skills and technology use on the academic success of new students at Universitas Terbuka (UT). A quantitative research method was employed, using an online survey distributed to new students across various study programs. Data analysis was conducted using SPSS statistical software to obtain descriptive and inferential results. The findings indicate that both self-directed learning skills and technology use positively and significantly impact students' academic success. Among these factors, technology use has a greater influence. The combination of high self-directed learning skills and effective technology use significantly enhances learning outcomes. This study is limited to a sample of new students and utilizes a survey method. The implications of these findings suggest the need for developing more effective learning programs, educational policies supporting technology use, and additional academic support for new students. Recommendations for future research include providing specialized technology training, developing comprehensive orientation programs, and conducting studies with larger samples and qualitative approaches for deeper insights.